9.2k views
0 votes
X + 2y - 3z = 11
2x + y - 2z = 9
4x + 3y + z = 16

1 Answer

4 votes

Answer:

X + 2y + -2y + -3z = 11 + -2y

2y + -2y = 0

X + 0 + -3z = 11 + -2y

X + -3z = 11 + -2y

X + -3z + 3z = 11 + -2y + 3z

-3z + 3z = 0

X + 0 = 11 + -2y + 3z

X = 11 + -2y + 3z

2)2x + -1y + y + 2z = 9 + y

-1y + y = 0

2x + 0 + 2z = 9 + y

2x + 2z = 9 + y

2x + 2z + -2z = 9 + y + -2z

2z + -2z = 0

2x + 0 = 9 + y + -2z

2x = 9 + y + -2z

x = 4.5 + 0.5y + -1z

3)
4x+3y+z-\left(3y+z\right)=16-\left(3y+z\right)\\4x=16-3y-z\\(4x)/(4)=(16)/(4)-(3y)/(4)-(z)/(4)\\= \frax{16-3y-zc}{4}

User Oluies
by
5.3k points